Excellence in Pediatric Physical Therapy Education: Recommendations and Action Items. Issue 2 (27th April 2023) - Birkmeier, Marisa; Lundeen, Heather; Furze, Jennifer; Moore, James G.; Dannemiller, Lisa; Anderson, Deborah
Abstract : Purpose: This special communication identifies evidence-based recommendations and offers action items to facilitate the uptake of new knowledge from the National Study of Excellence in Pediatric Physical Therapy Education (NSE-Peds). Summary of Key Points: The NSE-Peds identified a conceptual framework consisting of 4 key dimensions and associated elements that dynamically interact to prepare future physical therapists to meet the needs of society. The conceptual framework serves as the Knowledge Creation component of the knowledge to action (KTA) framework, but translation into practice requires the Action Cycle, the second component of the KTA framework. Recommendations and action items provide tangible products derived from the NSE-Peds conceptual framework for application in the Action Cycle. Conclusions: Using the KTA framework, implementation of the recommendations at the level of the individual, program, and organization should enhance pediatric physical therapy education and ultimately physical therapy care provided to children and families.